Stakeholders Reflect on Challenges Facing Early Childhood Education in the Winneba Municipality of Ghana. What do they say? - Jinapor, Ahmed (Advances in Social Sciences Research Journal, 2014)
The study provides an overview of challenges confronting early childhood education in the Winneba municipality of the central region of Ghana. It looks at factors that might have contributed to such challenges and what measures can be put in place to address them. Using a descriptive survey type approach, 17 participants consisting of early childhood educators, heads of early childhood centers, parents, and the National coordinator of Early Childhood programmes in Ghana participated in the study. Findings revealed that among the challenges associated with early childhood education in the Winneba municipality include; public prejudice about the relevance of early childhood educational programs to the child’s education and development, lack of parental involvement and commitment to early childhood education, lack of teaching staff and infrastructure, and institutional barriers. Reasons identified for such challenges included lack of education on the part of the public about the place and relevance of early childhood education in the total educational setup. Recommendations manifesting in sensitization and education, partnership and commitment by the public were among the many suggestions provided by participants in addressing most of the identified challenges. Keywords: Early Childhood Education, Challenges, Winneba Municipality, Stakeholders, Ghana.